INVESTIGATION OF STRUCTURAL CHARACTERISTICS OF INITIAL SUBSTANCES OF IBUPROFEN AND MICRONIZATION IMPACT - N. N. Lobanov; N. S. Knuchua; YU. A. Obidenko; R. A. Abramovich (Антибиотики и Химиотерапия)
Structural characteristics of ibuprofen substances manufactured by different firms and the impact of micronization on them were compared. The study showed that the use of X-ray diffraction methods was necessary for certification of medicinal (crystalline) since only such methods provided information on the substance crystal structure, the molecular state and polymorphous forms.